The influence of anxiety on pain perception and its repercussion on endodontic treatment: a systematic review - Farias, Zilda Betânia Barbosa Medeiros de; Campello, Camilla Porto; da Silveira, Márcia Maria Fonseca; Moraes, Sandra Lúcia Dantas; do Egito Vasconcelos, Belmiro Cavalcanti; Pellizzer, Eduardo Piza [UNESP] (Springer Nature, 2023)
Objective: To evaluate the influence of dental anxiety on the perception of pain before and during endodontic treatments. Materials and methods: The PRISMA checklist was followed. A search was conducted in Scopus, Medline/PubMed, The Cochrane Library, and Web of Science databases. Based on PECOS criteria, the first outcome was a possible association between pre-operative pain and anxiety. The second outcome was a possible association between intraoperative pain and anxiety. The type of studies was observational. The JBI Critical Appraisal Checklist was used to evaluate the methodological quality of articles. The certainty of the evidence was analyzed using the GRADE approach. Results: Four articles were included with a total of 471 patients. Two studies found a positive association between pain and pre-endodontic treatment anxiety. Three studies investigated the relationship between anxiety and intraoperative pain; two identified an extremely significant positive association. One article noted that anxiety influences pain expectancy. The studies were of good quality as assessed by the JBI Critical Appraisal Checklist for cross-sectional studies. However, the certainty of the evidence was considered low and very low. Conclusions: Dental anxiety can be directly associated with pre- and intraoperative pain during endodontic procedures. Clinical relevance: It is necessary to identify patients with dental anxiety to employ therapies to bring their anxiety under control, avoiding the increase of endodontic infections, and the postponement and evasion of endodontic treatments.
Keywords: Dental anxiety; Endodontics; Pain; Root canal therapy; Systematic review